PRINSIP TABAYYUN DALAM SURAH AL-HUJURAT AYAT 6: ANALISIS MULTIDISIPLINER PERSPEKTIF TAFSIR, KOMUNIKASI DAN LITERASI DIGITAL - Emrida Harahap; Dina Mariana Nasution; Fakhrul Falah Daulay; Wahdini; Mohd. Rafiq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has accelerated the flow of information, but it has also created serious challenges, including the spread of hoaxes, disinformation, and information manipulation through social media. In this context, the concept of tabayyun as stated in Qur'an Surah Al-Hujurat verse 6 is highly relevant as a foundation for communication ethics and digital literacy. This study aims to analyze the principle of tabayyun from the perspectives of Qur’anic exegesis (tafsir), communication studies, and digital literacy through a multidisciplinary approach. The research employs a library research method using a thematic interpretation (tafsir maudhu’i) approach and descriptive-qualitative analysis. Data sources were obtained from classical and contemporary tafsir literature, scientific journals, theses, dissertations, and recent books related to digital communication and media literacy. The findings reveal that tabayyun in Surah Al-Hujurat verse 6 encompasses three main dimensions: epistemological, ethical, and social. From the tafsir perspective, tabayyun is understood as the obligation to verify information before believing or disseminating it. From the communication perspective, tabayyun functions as a communication ethic that emphasizes accuracy, responsibility, and information validity. Meanwhile, from the digital literacy perspective, tabayyun serves as an essential principle for fostering critical thinking, fact-checking skills, and media awareness in the digital era. This study concludes that the principle of tabayyun can serve as both a normative and practical framework for developing a healthy and responsible digital literacy culture in modern society.